Improving Student Learning Outcomes in Reflection Learning (Geometric Transformation) through the Problem Based Learning Model for Class XI SMAN 4 Palu - Lail, Renova Mi’rojul; Hasbi, Muh.; Purwanti, Purwanti (International Journal on Advanced Science, Education, and Religion, 2025)
This research applies Classroom Action Research (PTK). This research was conducted in class XI of SMA Negeri 4 Palu, with the research process carried out in the even semester of the 2024/2025 school year, adjusted to the schedule of mathematics lessons in the class. The results showed an increase in the percentage of students' completeness, with cycle I reaching 47.05% and cycle II reaching 88.23%. This indicates that the application of the Problem Based Learning model contributes positively to the improvement of student learning outcomes on material reflection (geometric transformations) in class XI SMA Negeri 4 Palu. The application of the Problem Based Learning model that focuses on real contexts relevant to students can facilitate understanding of mathematical concepts more effectively. Solving real problems through the Problem Based Learning model is expected to prepare students to face realistic problems that they may face in the future.